A Rare Case: Amegakaryocyte Trombocytopenia As Early Manifestation Of Juvenile Systemic Lupus Erythematosus - Yeni Amalia; Wisnu Barlianto Susanto Nugroho (Jurnal Kesehatan Islam : Islamic Health Journal, 2020)
ABSTRACTBACKGROUND Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which results in inflammation and eventual damage in a broad range of organ systems. Trombocytopenia is a common complication in patients with SLE, but amegakaryocyte trombocytopenia (AMT) is a rare disorder in SLE that characterized by isolated thrombocytopenia as a consequence of a marked decrease in or total absence of megakaryocytes in an otherwise normal bone marrow.CASE Lu, a wellnourished 13 y.o girl, complaining for high fever for 2 weeks, diminished body weight, artralgia, furunculosis, oral apthae and palour for 1 year, and bruising extremities for 2 motnhs. There was hepatosplenomegali. Laboratory findings: Hb 8.8 gr/dL, hct 27%, leucocytes 1.000/µL (ANC 230/µL), trombocytes 25,000/µL. Bone marrow puncture revealed amegacaryocyte thrombocytopenia, absence of megacaryocyte while erythropoesis and granulopoesis were normal. Anti ds DNA 223.8 iu/ml (+); ANA test 101.7 unit (+), microalbumin urine 10 mcg/mg (-), C3 complement 40 mg/dL (¯), ACA IgM 20.6 U/ml (+), ACA IgG 17.3 U/mL (+). The case fulfilled 5 criteria of ACR for SLE. The patient administered ceftazidim and gentamycin for febrile neutropenia, and high dose methylprednisolon injection for SLE.